Konsep dan Habits of Mind Siswa Kelas VI SDIT Persatuan Islam 01 Brebes pada Materi Halal dan Haram dalam Islam dengan Aplikasi Baamboozle untuk Meningkatkan Keaktifan dan Berpikir Kreatif - Annisa Ilma Azzahro; Haris Diar Rizki; Fatikhul Birri; Regy Permatasari; Siti Nurhalishah (EduInovasi: Journal of Basic Educational Studies, 2026)
This study aims to analyze the implementation of digital game-based learning using Baamboozle in Islamic Religious Education (IS) teaching on halal and haram (permissible) topics in elementary schools. The focus of the study was directed at increasing students' learning engagement and creative thinking skills, as well as strengthening their Habits of Mind (Habbits of Mind) during the learning process. The study used a qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that the use of Baamboozle created an interactive learning environment, encouraged active student participation, and increased courage in expressing opinions and working collaboratively in groups. Furthermore, students demonstrated the development of Habits of Mind, such as persistence in problem-solving, flexibility of thinking, the ability to control impulses, and metacognitive awareness of their thinking processes. These findings indicate that the integration of gamification-based digital media in Islamic Religious Education (IS) learning not only contributes to conceptual understanding of the material but also supports the development of students' character and reflective thinking patterns.